2019
DOI: 10.15388/omee.2019.10.00004
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Determine the Closure or Jeopardize the Continuity of a Micro and Small Enterprise

Abstract: This paper explores the factors that determine the closure or jeopardize the continuity of micro and small enterprises (MSEs). We investigated the determinants of failure from the entrepreneur’s perspective using a qualitative approach, and five variables emerged. We discovered that there are internal and external variables that impact on an enterprise’s continuity, which are themselves correlated. We applied a formula to determine which variable had a higher weight, considering values ranging from 0 to 1, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 48 publications
0
9
1
Order By: Relevance
“…As per the cutoff point set by Al-Sayaad et al ( 2006 ), the mean result for people and administrative factor and government support is indicated “Agree” for Likert scale level, the remaining variables indicated “neutral” level. Thus, the study done by Rascón and Velázquez ( 2019 ) the mean result of people and administrative factors is not similar to this study result.…”
Section: Resultscontrasting
confidence: 87%
See 2 more Smart Citations
“…As per the cutoff point set by Al-Sayaad et al ( 2006 ), the mean result for people and administrative factor and government support is indicated “Agree” for Likert scale level, the remaining variables indicated “neutral” level. Thus, the study done by Rascón and Velázquez ( 2019 ) the mean result of people and administrative factors is not similar to this study result.…”
Section: Resultscontrasting
confidence: 87%
“…The correlation between people and administrative factors is similar to the finding of Abdissa and Fitwi ( 2016 ) with the result of r = 0.342. The other study was done by Rascón and Velázquez ( 2019 ) people and administrative factors had a positive relationship with other study variables with the value of r = 0.60 with significant p value. This study result is similar to this study.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We found that the research on the mortality risk of MSE is increasing because entrepreneurship is a global trend, as it is considered a driver for economic growth [4,39,40] and a contributor to the creation of jobs and innovations [2]. Therefore, the management of MSEs has gained importance at the social, governmental, business, and academic levels [6].…”
Section: Descriptive Analysismentioning
confidence: 99%
“…MSEs represent the majority of the total number of companies in most countries [6,7] and, because of their diversity, they are generally classified regarding the number of employees, annual turnover, and amount of total annual assets [8]. MSEs are fragile and are exposed to risks in the initial years of operation, a period in which entrepreneurs are learning to operate a new business [9].…”
Section: Introductionmentioning
confidence: 99%